Achieving Survival of Social Enterprise Through Entrepreneurial Marketing: An Empirical Analysis of Nigeria - NWANKWO Cosmas Anayochukwu; KANYANGALE MacDonald Isaac (Foundations of Management)
The application of entrepreneurial marketing (EM) strategies to the sustainability of profit and non-profit making ventures has drawn critics from practitioners and academic domains. Many have argued that EM dimensions are designed for profit marking ventures and not for profit venture. This informed the need to examine the effect of EM on the survival of social enterprises (SEs) in Nigeria. The study selected SEs staff in Anambra State, Nigeria using a quantitative research approach. Data were collected from 387 SE staff using a structured questionnaire. Hypotheses were tested using International Business Machine Statistical Package for the Social Sciences (IBM-SPSS) and International Business Machine -Statistical Package for the Social Sciences - Analysis of Moment Structures (IBM-SPSS-AMOS) version 27 that runs exploratory and confirmatory factor analysis and structural equation modelling (SEM). The findings revealed that all the EM dimensions, except market sensing, have significant and positive effect on the survival of SEs in Nigeria. Therefore, the study concluded that EM has significant effect on the survival of SEs in Anambra State, Nigeria. The study recommended that practitioners should adopt and implement EM dimensions as the basic enablers that would sustain the existence of SEs in both Nigeria and beyond.